2019
DOI: 10.1039/c9na00599d
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-driven carrier extraction enhancement in photovoltaic cells based on arrays of subwavelength light funnels

Abstract: Texturing the front surface of thin film photovoltaic cells with ordered or disordered arrangements of subwavelength structures is beneficial in terms of efficient light harvesting as well as efficient carrier extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…[ 17–19 ] Also, PV cells based on LF arrays were reported to provide enhanced PV performance due to inherent inverted configuration. [ 20,21 ] Recently, it was suggested that the mechanism for the superior absorption in LF arrays is inherently distinct from that of NP arrays; proximity effects in compact LF arrays result in an elevated excitation of the LFs, as opposed to NP arrays in which a reduction in the excitation accompanies the densification of the arrays, as discussed earlier. [ 12 ] Consider, for example, illumination of an isolated LF, in the shape of inverted cone, from an infinitely long cylindrical glass rod with the HE 11 waveguide mode.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17–19 ] Also, PV cells based on LF arrays were reported to provide enhanced PV performance due to inherent inverted configuration. [ 20,21 ] Recently, it was suggested that the mechanism for the superior absorption in LF arrays is inherently distinct from that of NP arrays; proximity effects in compact LF arrays result in an elevated excitation of the LFs, as opposed to NP arrays in which a reduction in the excitation accompanies the densification of the arrays, as discussed earlier. [ 12 ] Consider, for example, illumination of an isolated LF, in the shape of inverted cone, from an infinitely long cylindrical glass rod with the HE 11 waveguide mode.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20–25 ] It was also suggested that the unique inverted shape of the LFs results in a contact‐selectivity enhancement, which promotes efficient carrier extraction and additional contribution to the already high photocurrents. [ 26 ] In a recent publication, we showed that the absorption mechanism in LF arrays is fundamentally different from NP arrays; proximity effects in dense LF arrays induce higher excitation levels inside the individual LFs in contrast with the NPs where a decrease in the excitation level is recorded, as discussed earlier. [ 27 ] This unique absorption mechanism in dense LF arrays is the key for the possible enhancement of photovoltage that is concurrent with the photocurrent enhancement.…”
Section: Introductionmentioning
confidence: 77%
“…Carrier collection from photovoltaic (PV) cells based on arrays of subwavelength structures was previously reported. [11,12,37,[56][57][58][59][60] Carrier collection from LF arrays [61][62][63][64] and DSSS arrays [48] was numerically described previously using axial junction configuration with a shallow degenerated n-type emitter at the top of the arrays and a p-type absorber. The dependency on array geometry (LF D b values), surface recombination, and absorber doping concentrations was considered, and it was shown how the enhanced broadband absorption is translated into elevated values of short-circuit current ( J sc ) as compared with NP arrays.…”
Section: Resultsmentioning
confidence: 99%